Intention to purchase alternative tobacco products as a function of smoking status and responses to advertising, packaging, and sensory experiences. (July 2022) - Sharma, Akshika; June, Kristie M.; Norton, Kaila J.; Fix, Brian; Bansal-Travers, Maansi; Rees, Vaughan W.; J.O'Connor, Richard
Highlights: The study extensively explores the perceptions, intentions to purchase and reactions (in the form of valence and arousal) towards different levels of exposure to two products. The participants (current, former and never smokers) were exposed to products advertisements, packaging, smell and handling as well as taste option was given to current smokers. Using a between subjects design for assessment of perceptions and intentions after different exposures our paper provides results from multivariate regression models and repeated measures anova. Results show that, when given a choice, cigarette smokers prefer to use Nicotine gum over Camel snus, as measured by intentions to purchase, concluding that Camel Snus has low acceptance in US population and might not be a useful smoking cessation tool. Abstract: Introduction: Tobacco manufacturers design and marketed products with appealing sensory characteristics to drive product uptake and continued use. We assessed smokers' and non-smokers' cognitive, affective, and sensory responses to Camel Snus (CS) and Nicotine gum (NG) to gauge future intentions to use. Method: In a single laboratory session, 348 participants (including current smokers and nonsmokers in Buffalo, NY and Boston, MA) were exposed to CS and NG products in counterbalanced order. Exposure involved a cumulative set of 3 steps in which participants i) viewed an advertisement; ii) viewed the packaging, and iii) touched and smelled the product, without actual use. Current daily and non-daily smokers were invited to undertake a fourth exposure step by sampling the product. Following product exposure, participants completed perception measures and reported future intentions to use either product at the end of the survey. After each exposure, participants' reported feelings of valence and arousal. Results: Smokers reported greater preference to try NG (63.8%) compared with CS (17.4%) or neither (18.8%), whereas majority of nonsmokers preferred neither product (64.3%) (p < 0.01). Of those offered to sample the products, 78.3% daily smokers and 68.4% non-daily smokers opted to sample. When asked about intentions to try, a greater proportion of smokers stated a preference to try NG over CS, as did the small number of nonsmokers who expressed a preference. Conclusion: Intentions to try CS were low despite different levels of exposure to product, and this low product appeal and interest in use may translate to limited potential of CS to serve as a reduced harm product for smokers.